Efecte și implicații ale impozitării persoanelor fizice - Adrian Mihai INCEU; Dan Tudor LAZĂR (Revista Transilvană de Ştiinţe Administrative, 2002)
This paper is concerning with the very important effects what taxes on income have to various persons. The taxes, on various forms of income, have various effects on work, savings and consume – this paper emphasize some of this effects, what is true about this effects, what the data relieve.